2007
DOI: 10.1016/j.jmwh.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Connecticut Nurse‐Midwives

Abstract: Descriptive data on nurse-midwifery income, workload, job definitions, employment benefits, and clinical practices are limited. Information about nurse-midwifery practice today is important for the growth of the profession and for future policy initiatives. A survey of nurse-midwives in Connecticut was conducted in 2005. This article reports state-specific data about income, workload, job definitions, employment benefits, and clinical issues, such as vaginal birth after cesarean. Full-time midwives in Connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…This finding was in contrast to the survey of Connecticut CNMs (Holland & Holland, 2007) that found that gynecologic care was provided by 99% and primary care by 52% of respondents. Jevitt and Beckstead's (2004) survey of Florida CNMs found 76% of respondents provided gynecologic care and 43.2% provided primary care for women.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding was in contrast to the survey of Connecticut CNMs (Holland & Holland, 2007) that found that gynecologic care was provided by 99% and primary care by 52% of respondents. Jevitt and Beckstead's (2004) survey of Florida CNMs found 76% of respondents provided gynecologic care and 43.2% provided primary care for women.…”
Section: Discussioncontrasting
confidence: 99%
“…It may also indicate the relatively scarce provision of nurse-midwifery care in rural Colorado areas-areas that have limited access to other primary care providers and specialists and where CNMs would be more likely to provide full scope care. Finally, and not surprisingly, very few (7%) nurse-midwives provided newborn care, a rate lower than the approximate 15% reported in other statewide surveys (Holland & Holland, 2007;Jevitt & Beckstead, 2004). This likely reflects the fact that 99% of all respondents attended births in the inpatient setting and were employed by hospitals or a physician group, consistent with national trends (Schuiling et al, 2005).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Increasingly midwives and certified nurse-midwives in many Western countries are providing a broad spectrum of maternity care, often working alongside obstetricians, general practitioners or family physicians. [27][28][29][30] Many hospitals are also encouraging midwives and certified nurse-midwives to work autonomously when providing prenatal care, a trend that has been observed internationally despite the differences in organized health care structures between different countries. 27,[31][32][33] As nothing is currently known about how midwives collect family history or their attitudes around asking about consanguinity, we have explored both current practice and attitudes toward collecting this information within an ethnically heterogeneous population.…”
mentioning
confidence: 99%